Trends in Extension Research in India-A Case study - Girijesh Singh Mahra, B. Kumar, Neelam Bhardwaj and Debashis Dash, (Indian Journal of Extension Education, 2017)
Extension Education’ has established itself as a profession and a discipline with three important components ofteaching, research and service. The extension system of India has witnessed paradigm shift from ‘production led’to ‘farmers led’ system which in turn has transformed the researches in extension. Today, extension researches andteaching is being practiced by teachers and students in more than 70 State Agricultural Universities (SAUs), fourdeemed to be universities (DUs), one Central Agricultural University (CAU) and four Central Universities (CUs)with Agriculture Faculty. Furthermore, extension research is being carried out in more than 100 ICAR researchinstitutes and State Departments. The present study outlines the trends in extension research of two leadingAgricultural Institutes viz. ICAR-IARI, New Delhi and GBPUAT, Pantnagar based on indepth review of M.Sc. andPh.D. research work at respective Institutes. The present paper also reviews the extension research published in‘Indian Journal of Extension Education’. The findings showed that besides traditional areas of extension researchnew areas like ‘ecotourism’, ‘nutritional security’, ‘up scaling and out scaling of farm innovations’, ‘validation ofITK’s’ and ‘climate change adaptation’ has been picked up by extension researchers nationwide leaving aside theold notion of transfer of technology.